Analysis of content of the love and hate Scripts of antisocial persons - Gawda, Barbara (Studia Psychologica: Theoria et praxis, 2010)
Crucial to this study is to compare the content of the love and hate Scripts of persons diagnosed with antisocial personality. The literaturę points to the antisocial persons have some specific schemas and Scripts which deter mined their strong incapacity for love and the tendency to violence, anger and hate. There were examined 50 prisoners with antisocial personality di sorder, 30 prisoners without antisocial personality disorders, and 50 men non-prisoners without the antisocial tendencies. The subject matter of the analysis was narrative monological discourse. Ali participants had to de scribe the situations presented at the photographs: the love meeting and the ąuarrel. Then, the comparisons of the content of two Scripts were done. The results show the antisocial persons possess emotional knowledge linked to faulty beliefs, but they have problems in recognizing valence of emotions. They use cognitive strategies which elicit the difficulties in understanding the emotions.